ANALISIS EFEKTIFITAS PENERIMAAN PAJAK PENGHASILAN PADA KANTOR PELAYANAN PAJAK PRATAMA BANDA ACEH - Ratna Mutia (UNIVERSITAS SERAMBI MEKKAH, 2016)
This study entitled Effectiveness Analysis of Revenue Income Tax Office Primary In Banda Aceh. This research was conducted at the Tax Office Primary Banda Aceh as agency that manages its income tax revenue in the region. Planning and supervision of the tax is a crucial stage in the amount of tax revenue. One function that describes the tax planning is the budget (budget). In addition to the budget report can also be used as a tool to measure the effectiveness of that is by comparing the target with the realization to determine the performance that has been achieved. The purpose of this study was to determine whether the acceptance of Income Tax on the Tax Office Pratama Banda Aceh has been effective or appropriate for the target that has been set. The method used is quantitative and descriptive methods. To find out how effective income tax receipts to the Tax Office Primary Banda Aceh can be done by analyzing the ratio between the planned targets with realized. From the results of this study concluded that income tax revenue target in the STO Banda Aceh has not been fully realized. But supervision performed in income tax revenues are in accordance with the standards of supervision